Perancangan Sistem Informasi Pembayaran Uang Praktek Kerja Industri - Syamsiah; Diana Sukseswaty Lubis (STMIK Budi Darma, 2023)
The development of information and technology continues to increase, especially in the field of information, so it is very helpful in carrying out daily activities and activities. It is easy for people to access a variety of fast and accurate information, making the use of technology increasingly popular with all people. The information referred to here is information based on computer technology which is developing very fast, both in hardware and software. One of the applications of a practical money payment information system is using a website-based information system. The website is used in the application because the website is a place for user interaction. The website is used within the company to make it easier to access or input financial data in making practical payments. This study aims to facilitate the payment of internship money by designing a web-based information system. The existence of this system can make it easier for students to get information about paying internship money. And make it easier for Lkp Utama Jaya in the process of managing data for internship payments. The method used in this study uses qualitative methods. The design of a web-based practical money payment information system at Lkp Utama Jaya was built with the CI 3 Framework PHP (Hypertext Preprocessor) programming language and mysql database and for the ex-editor it used the Visual Studio Code application. The results of the research have been successfully implemented so that it is expected to be able to help students to find out information about payment of internship money more easily